2004
DOI: 10.1083/jcb.200312041
|View full text |Cite
|
Sign up to set email alerts
|

PKCα mediates TGFβ-induced growth inhibition of human keratinocytes via phosphorylation of S100C/A11

Abstract: Growth regulation of epithelial cells is of major concern because most human cancers arise from them. We demonstrated previously a novel signal pathway involving S100C/A11 for high Ca2+-induced growth inhibition of normal human keratinocytes (Sakaguchi, M., M. Miyazaki, M. Takaishi, Y. Sakaguchi, E. Makino, N. Kataoka, H. Yamada, M. Namba, and N.H. Huh. 2003. J. Cell Biol. 163:825–835). This paper addresses a question whether transforming growth factor β (TGFβ) shares the pathway with high Ca2+. On exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 26 publications
(41 reference statements)
2
54
1
1
Order By: Relevance
“…Thr 10 and Ser 94 (18), showed a binding mode similar to that of the wild-type protein. Endogenous S100A11 and cPLA 2 were pulled down by GST-ANXA1 added to the cell extracts (supplemental Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Thr 10 and Ser 94 (18), showed a binding mode similar to that of the wild-type protein. Endogenous S100A11 and cPLA 2 were pulled down by GST-ANXA1 added to the cell extracts (supplemental Fig.…”
Section: Resultsmentioning
confidence: 84%
“…4A). We previously showed that S100A11 functions as an essential mediator for growth suppression of NHK by high Ca 2ϩ and TGF␤ (18,19,21). S100A11 is phosphorylated by protein kinase C␣ as a prerequisite for translocation into the nucleus and induction of p21 WAF1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective knockdown studies of PKC␣ (via antisense oligonucleotides, RNA interference as well as pharmacological inhibitors), and biochemical studies using PKC isotypespecific cDNA (wt, constitutively active, and dominant negative), already strongly implicated a role of PKC␣ in the control of cell cycle machinery. Importantly, the biological responses obtained by the manipulation of PKC␣ were found to be cell-type specific (17); it promoted proliferation in some types of cells (human breast cancer cells, neonatal cardiomyocytes (22), and mediated cell cycle arrest in other cell types (epithelial cells) by inducing cyclindependent kinase inhibitors, p21 Waf1/Cip1 (23) and p27 Kip1 (24). The distinct responses are modulated by dynamic interactions with cell-type-specific anchoring proteins such as the receptor for activated PKC, vinculin, talin, ␤ 1 integrin, and caveolin.…”
Section: Discussionmentioning
confidence: 99%
“…S100 A11 has been detected in ovarian ascites 73 . S100 A11 (or calgizzarin) is known to regulate cell growth by inhibiting DNA synthesis 86,87 . S100 A12 is known to contribute to leukocyte migration in chronic inflammatory responses 88 .…”
Section: Proteins Associated With Cell Proliferationmentioning
confidence: 99%